Handbook of Teacher Education
X, 756 p.
Keywords: This book provides an international review of the current state of teacher education, with chapters from an international group of teacher educators. It focuses on major issues that are confronting teacher educators now and in the next decade. These include the impact of globalization on the profession of teaching, and how teacher education must deal with changing accountability requirements from governments and establish a set of minimum standards acceptable to enable a person to teach. The work also considers aspects of the three major phases of teacher education: the period prior to commencing in the profession, successful induction into the profession, and the ongoing professional development of teachers. Finally, it identifies ways in which new technologies can be used to improve the training and ongoing development of teachers. Cases from different countries are used to provide a rich base of data to help us understand how the profession is moving onwards.